Instructional Management Competency Development of Novice Instructors in College of Nursing Under the Praboromarajchanok Institute - Rungkarn Wutti (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purposes of this research study were to 1) study contexts of the instructional competency development for novice nursing instructors of nursing colleges under Praboromarajchanok Institute 2) develop and quality of a model for instructional competency development for novice nursing instructors of nursing colleges under Praboromarajchanok Institute 3) study a result of using a model for instructional competency development for novice nursing instructors of nursing colleges under Praboromarajchanok Institute. The population were novice instructors of nursing colleges under Praboromarajchanok Institute in Northern area of Thailand working in the first 3 years, directors and others involved in the development of novice instructors. The samples of the study were included 59 directors and others involved in the development of novice instructors and novice instructors. Data collections were literature review, interviews, focus groups and assessed by using a semi-structured interview questionnaires and recording forms. The data were analyzed with content analysis, mean and standard deviation percentage and test statistics with the Friedman Two-way ANOVA, and Wilcox on Singed-Ranks Test